2012
DOI: 10.1109/tcsii.2011.2173965
|View full text |Cite
|
Sign up to set email alerts
|

Linear Programming Design of Coefficient Decimation FIR Filters

Abstract: Abstract-The coefficient decimation technique for reconfigurable FIR filters was recently proposed as a filter structure with low computational complexity. In this brief, we propose to design these filters using linear programming taking all configuration modes into account, instead of only consider the initial reconfiguration mode as in previous works. Minimax solutions with significantly lower approximation errors compared to the straightforward design method in earlier works are obtained. In addition, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This basic idea is motivated by [7] that taking all desired modes into consideration can give better results for the design of reconfigurable coefficient decimation FIR filters. However, as the cascade structure of the FRM filters, linear programming (LP) used in [7] will not be appropriate for the optimal design of the FRM based reconfigurable filter banks. Alternatively, we formulate the optimal design of the FRM based reconfigurable filter banks as an SDP problem.…”
Section: Our Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This basic idea is motivated by [7] that taking all desired modes into consideration can give better results for the design of reconfigurable coefficient decimation FIR filters. However, as the cascade structure of the FRM filters, linear programming (LP) used in [7] will not be appropriate for the optimal design of the FRM based reconfigurable filter banks. Alternatively, we formulate the optimal design of the FRM based reconfigurable filter banks as an SDP problem.…”
Section: Our Proposed Methodsmentioning
confidence: 99%
“…It has been demonstrated that, for the design of reconfigurable coefficient decimation FIR filters, taking all reconfiguration modes into consideration can give better results [7]. However, as the cascade structure of the FRM filter, linear programming (LP) used in [7] will not be appropriate for the optimal design of the FRM based reconfigurable filter banks. In earlier works, semidefinite programming (SDP) [8] has been employed for the optimal design of basic single mode FRM filter [9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the degree of control over the cutoff frequency they offer, the VCF filters can be categorized as the VCF filters with discrete control over the cutoff frequency (variable-coefficient filters [4][5][6][7][8][9][10][11][12][13][14], coefficient decimation based filters [15][16][17][18][19], frequency response masking based filters [20][21][22][23][24][25]) and the VCF filters with continuous control over the cutoff frequency (all-pass transformation based filters [26][27][28][29], fractional delay structure based filters [30][31][32], frequency transformation based filters [33][34][35][36][37], SPA based filters [38][39][40][41][42][43][44][45][46][47][48][49][50]…”
Section: Fixed-coefficient Vcf Filtersmentioning
confidence: 99%
“…This optimization based technique considered the required decimation factors beforehand to generate additional constraints for the prototype filter design, unlike the conventional technique which uses just the basic filter design specifications to obtain the prototype filter coefficients. As a result, the prototype filters obtained using the optimization technique proposed in [103] showed better stopband attenuation…”
Section: Development Of Spectrum Sensing Schemes Using Proposed Variamentioning
confidence: 97%
“…It can be noted that the conventional CDM and the various CDM based VDFs and filter banks also faces the same stopband attenuation deterioration problem. To address this problem in the CDM, a linear programming based filter design technique was proposed in [103]. This optimization based technique considered the required decimation factors beforehand to generate additional constraints for the prototype filter design, unlike the conventional technique which uses just the basic filter design specifications to obtain the prototype filter coefficients.…”
Section: Development Of Spectrum Sensing Schemes Using Proposed Variamentioning
confidence: 99%